The Administration of Epididymis Extract Increased the Testosterone Concentration without Affects the Dihydrotestosterone Concentration in Local Male Goat - Nanda Yuliansyah; Muslim Akmal; Tongku Nizwan Siregar; Sri Wahyuni; Mahdi Abrar; Syafruddin Syafruddin; Gholib Gholib; Farida Athaillah (The Faculty of Veterinary Medicine of Syiah Kuala University, 2017)
This study was aimed to determine the effect of epididymis extract (EE) on the testosterone and dihydrotestosterone (DHT) level of local male goat. An experimental study was performed using a completely randomized design (CRD) pattern of one-way analysis of variance (ANOVA). 15 local male goats aged 1.5 years with body weight 14-16 kg were used in this study. The K0 group as a control group, injected with only 1 ml physiological saline, while each KP1, KP2, KP3, and KP4 groups treated with multilevel EE dose, ie 1, 2, 3, and 4 ml / goat for 13 consecutive days. At the end of treatment (day 14th), testes, epididymis (caput, corpus, and cauda) and ductus deferens samples were taken through the close-castration method for examining the testosterone and DHT concentration by using enzyme-linked immunosorbent assay (ELISA) technique. Data gathered were later analyzed using ANOVA followed by Tukey’s HSD in SPSS 16.0 for Windows. The result showed that the average concentration of testosterone on K0, KP1, KP2, KP3, and KP 4 in testis respectively were 10.00±2.64 ng/ml; 7.66±2.51 ng/ml; 10.00±6.55 ng/ml; 0.66±0.57 ng/ml; 11.66±7.37 ng/ml; caput epididymis; 5.00±1.73 ng/ml; 2.33±1.52 ng/ml; 5.00±2.64 ng/ml; 1.33±0.57 ng/ml; 5.66±1.15 ng/ml; corpus epididymis; 1.33±0.57 ng/ml; 0.66±0.57 ng/ml; 4.00±2.64 ng/ml; 0.66±0.57 ng/ml; 4.33±2.30 ng/ml; cauda epididymis: 1.00±0.00 ng/ml; 0.66±0.57 ng/ml; 1.66±0.57 ng/ml; 1.00 ± 0.00 ng/ml; 2.00±1.73 ng/ml; ductus deferens: 3.66±2.51 ng/ml; 0.66±0.57 ng/ml; 3.00±1.00 ng/ml; 1.00±0.00 ng/ml and 3.66±1.15 ng/ml. While the average concentration of DHT on K0, KP1, KP2, KP3, and KP 4 in testis respectively; 10.00±2.64 ng/ml; 7.66±2.51 ng/ml; 10.00±6.55 ng/ml; 0.66±0.57 ng/ml; 11.66±7.37 ng/ml; caput epididymis; 5.00±1.73 ng/ml; 2.33±1.52 ng/ml; 5.00±2.64 ng/ml; 1.33±0.57 ng/ml; 5.66±1.15 ng/ml; corpus epididymis; 1.33±0.57 ng/ml; 0.66±0.57 ng/ml; 4.00±2.64 ng/ml; 0.66±0.57 ng/ml; 4.33±2.30 ng/ml; cauda epididymis: 1.00±0.00 ng/ml; 0.66±0.57 ng/ml; 1.66±0.57 ng/ml; 1.00 ± 0.00 ng/ml; 2.00±1.73 ng/ml; ductus deferens: 3.66±2.51 ng/ml; 0.66±0.57 ng/ml; 3.00±1.00 ng/ml; 1.00±0.00 ng/ml and 3.66±1.15 ng/ml. Statistical analysis showed that the administration of EE only increased testosterone concentration in testes had significant effect (P 0.05). From this study, it can be concluded that the EE has the potential to improve spermatogenesis and sperm quality through increasing the testosterone concentration in the local male goats.